PERAN SUMBER DAYA MANUSIA, STANDAR AKUNTANSI PEMERINTAHAN, PEMANFAATAN TEKNOLOGI INFORMASI, PENGENDALIAN INTERN DAN KOMITMEN ORGANISASI DALAM MENINGKATKAN KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KOTA SERANG - Rohman, Abdul; Hasanudin, Agus Ismaya; Lestari, Tri (JURNAL RISET AKUNTANSI TIRTAYASA, 2020)
The purpose of this research is to get the evidence about effect of human resources, government acconting standards, information technology untilization, internal control, and organizational commitment on the quality of local govermment finance.The population in this study is the Regional Device Organization (OPD) Kota Serang with samples secretary, heads of division and staff doing financial activities. Sample were selected by purposive sampling method. Data obtained by distributing questionnare directly to 128 responden and 82 quesionnare that can be processed. Analysis of data using multiple linear regressioner with SPSS (Statistics Product and Service Solution) 25Keyword : Human resources, Government acconting standards, Information technology untilization, Internal control, Organizational commitment, govermment financial statement quality.